Conformational stabilization of isatin Schiff bases – biologically active chemical probes. Issue 17 (6th February 2017) - Smirnov, Andrey S.; Nikolaev, Dmitriy N.; Gurzhiy, Vlad V.; Smirnov, Sergey N.; Suslonov, Vitaliy S.; Garabadzhiu, Alexander V.; Davidovich, Pavel B.
Abstract : Two ways of conformation stabilization for isatin Schiff bases (group of biologically active compounds) are reported here: complexation with metals that stabilize E -conformer and substitution in the 4 th position of isatin core stabilizing Z -form. Abstract : Isatin Schiff base derivatives have a wide range of biological effects. Unfortunately, these compounds possess a serious topological shortcoming: the conformational E ⇆ Z interconversion. Two ways of conformation stabilization are reported here: complexation with metals that stabilize the E -conformer and substitution in the 4 th position of the isatin core stabilizing the Z -form.